Bridges to Effective Learning through Radio - Chandar, Usha; Sharma, Ramesh (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
Indira Gandhi National Open University has been allotted 40 FM radio stations from which to broadcast educational programmes for the benefit of students and general public in India. These FM radio stations, delivered through the Gyan Vani network, cater to learners seeking to gain knowledge in the areas of basic, primary, higher, and extension education. Radio programming covers various subject areas. It is anticipated that the opening of India's airwaves will prove beneficial to the nation's general population, thus fostering the democratising principals of empowerment, advocacy, and community participation. This study examines the results of a survey conducted to obtain feedback from a representative sample of the Gyan Vani network's projected audience. The survey focused on audience's perceived need for a radio channel dedicated exclusively to educational programming; it also provided an opportunity for respondents to suggest possible programme content and formats. Respondents, in general, indicated that they looked towards the network Gyan Vani to fulfil personal and educational goals by offering certified vocational courses, coaching for entrance exams, updated information on careers, courses, etc.